Psychoactive substance use in male patients hospitalized in an acute psychosis clinic and its effect on clinical variables - Sancak, Barış; Özgen, Güliz; Özer, Ürün; Uzun, Utku (Journal of Dependence, 2014)
Objective: Psychoactive substance use is common in psychotic patients and its prevalance was reported to be 3.2% in schizophrenia and 3.5% in bipolar disorder in Turkey. Substance use has been found to aggravate positive symptoms, increase the number of hospitalizations and relapses, and to be related with suicidal ideation, agression and noncompliance to treatment. In this study, it was aimed to determine the rate of subtance use in male patients hospitalized in an acute psychosis clinic, and investigate clinical and sociodemographic parameters which might be related with subtance use. Method: Records of patients who were hospitalized between 01 March-31 May 2014 have been examined retrospectively. Sociodemographic and clinical data forms have been filled. Data of physical restraints have been obtained from physical restraint registry book. Results: In this study, ongoing substance use was detected in 109 of 351 patients (31.1%). Substance use was found to be more common in affective disorders (21.8%) than psychotic disorders (14%). Substance users were younger (mean age 28.9±7.4) than patients who do not use any substance (37.5±12.2) (p<0.001). It was also found that 81.7% of substance users, but only 54.6% of patients who do not use any substance consisted of single patients (p<0.001). Substance users had shorter history of mental illness (5.67±5.8 years) than patients who do not use any substance (10.45±9.7 years) (p<0,001). In psychotic and affective patients who have alcohol or substance use, the number of hospitalizations (p=0.05, t=1.9) and the rate of physical restraint (36.7%) were higher (p=0,001). Conclusion: Patients who have psychoactive substance use and their relatives should be informed and referred to alcohol-substance treatment clinics if necessary. In these patients effective treatment of substance use may affect the prognosis positively.